ANALISIS FINANSIAL USAHA DODOL SALAK (STUDI KASUS: UD MANDIRI DI DESA PANGU SATU KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA) - Kathleen Iin Grace Sagay; Agnes Estephina Loho; Melissa Lady Gisela Tarore (AGRI-SOSIOEKONOMI, 2019)
The objective of this research is to analyze the level of financial feasibility of dodol "UD Mandiri" in Pangu Satu Village, Ratahan Timur Sub-District, Southeast Minahasa Regency. This research was conducted from November 2018 to April 2019. Research Methods Case Study. The data used are primary data and secondary data. Primary data is obtained from direct interviews with business owners UD Mandiri. Whereas secondary data is obtained from companies, books available at local bookstores and on the internet such as Google Scholar to access articles from various scientific journals and theses from other universities relating to the topic of this research are mainly concerned with financial analysis.Analysis of existing data using qualitative methods and quantitative methods. Qualitative methods are carried out to find out the dodol business characteristics that are presented in non-financial aspects in descriptive form, tables, charts or images, graphics such as process/production aspects, marketing aspects, legal aspects, environmental aspects,environmental aspects. Quantitative methods uses quantitative numbers regarding financial feasibility such as Net Present Value (NPV), Net B / C Ratio, Internal Rate Return (IRR), Payback Period (PP). There search result showed by using its own capital, UD Mandiri salak dodol business is declared feasible with an NPV value of Rp103.045.440, IRR (Internal Rate Return) or investment return of 60%, more than the UKM interest rate ( 6%) and Net B / C Ratio of 1,012, greater than one and payback period for two years.*jnkd+erprm*